Potencial evocado miogênico vestibular (VEMP) na evolução da mielopatia associada ao HTLV-1 - Lilian Felipe (2011)
Introduction: HTLV-1 associated Myelopathy / Tropical Spastic Paraparesis (HAM / TSP) is a chronic progressive demyelinating disease that affects the spinal cord and the brain's white matter. The Vestibular Evoked Myogenic Potential (VEMP) is a neural response from three-neuron reflex arc involving the inner ear, the brainstemand vestibular-spinal pathway. This test was evaluated in HTLV-1 infected individuais by cross-sectional study was more change in HAM / TSP compared to examine the asymptomatic individual. It is important to know the VEMP value for the monitoration of asymptomatic patients with symptoms but without the HAM / TSP criteria and the evolution to incipient neurological disorders. Objective: Longitudinal evaluation of theresults of VEMP in subjects with HTLV-1 in different disease progression stages, ranging from asymptomatic to individuais with established HAM / TSP. Methods: Prospective and comparative study, from 2006 to 2009. The participants underwent VEMP with an interval of six months, totaling four serial assessments. Were evaluated adults between 21 and 73 years, of both genders were divided into four groups: control group, consisting of healthy seronegative donors of the FoundationCenter of Hematology in Minas Gerais (Hemominas) and three other groups study comprised of HTLV-1 infected individuais, as follows: asymptomatic infected subjects, possible HAM / TSP and with defined HAM / TSP from the open cohort followed by the Group for interdisciplinary Research in HTLV (GIPH). For the record VEMP, were used tone burst at an intensity of 118 dB and in band-pass filter from 10Hz to 1500Hz, with 200 stimuli presented at a frequency of 1Hz with record time of60 ms. In the analysis, we considered P13 and N23 latency and amplitude. The amplitude variation was controlled by the asymmetry index. Results: 90 subjects, whereas 30 (33,3%) to the control group and 60 (66,7%) of the seropositive group, subdivided into subgroups 18 (30%) asymptomatic patients 25 (41,7%) with probableHAM / TSP and 17 (28,3%) defined HAM / TSP. A higher frequency of VEMP absent in individuais with HAM / TSP and no abnormal test reverted to normal examination or any absent VEMP test reverted to an increase of latency. Thus the altered response in VEMP latency prolongation has changed for the absence of evoked response to the evolution of neuronal damage. In the survival curve, it was observed that during the surveillance was more likely to change in VEMP response in ali groups, this finding being more pronounced in subjects with HAM / TSP, and there isa progression to a worse response. Conclusion: Vestibular Evoked Myogenic Potential (VEMP) was useful to monitoring HTLV-1 individuais and HAM / TSP progression, although is a progressive and slow course neurological disease. Possibly, asymptomatic individuais infected with HTLV-1 with altered VEMP will have more chance to develop neurological disease than those with normal VEMP.